2021
DOI: 10.1126/sciadv.abg4398
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of replication-independent DNA mismatch repair drives a 5-methylcytosine deamination mutational signature in cancer

Abstract: DNA mismatch repair is essential for protecting the human genome from damage induced by 5-methylcytosine deamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…Our study identified three components (MSH2, MSH6 and PCNA) of the post-replicative MMR complex as ZFP57 interactors by LC–MS/MS analysis. The MMR pathway is essential for repairing 5mC deamination because the MSH2/MSH6 heterodimer recognizes G:T mismatches and recruits downstream proteins for correction [ 15 , 26 ]. Indeed, defects of MMR genes increase the genome-wide mutation rate of methylated CpGs in cancer [ 15 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study identified three components (MSH2, MSH6 and PCNA) of the post-replicative MMR complex as ZFP57 interactors by LC–MS/MS analysis. The MMR pathway is essential for repairing 5mC deamination because the MSH2/MSH6 heterodimer recognizes G:T mismatches and recruits downstream proteins for correction [ 15 , 26 ]. Indeed, defects of MMR genes increase the genome-wide mutation rate of methylated CpGs in cancer [ 15 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MMR pathway is essential for repairing 5mC deamination because the MSH2/MSH6 heterodimer recognizes G:T mismatches and recruits downstream proteins for correction [15,26]. Indeed, defects of MMR genes increase the genome-wide mutation rate of methylated CpGs in cancer [15,27]. Also, Msh2/Msh6 knockout mice show higher cancer predisposition, microsatellite instability and mutator phenotype [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…H3K36me3 marks the gene bodies and exons of active genes in humans (F. Li et al 2013; Huang, Gu, and Li 2018; Fang et al 2021; Aymard et al 2014; Sun et al 2020), and reduced mutation rates in active genes, regions, and gene bodies, as a consequence, have been observed in humans and other animals (Moore et al 2021; Akdemir et al 2020; R. Li et al 2021; Katju et al 2022a; Supek and Lehner 2017).…”
Section: Introductionmentioning
confidence: 99%
“…That the localization of DNA repair proteins can drive such mutation biases has been well-established in humans (Supek and Lehner, 2015, 2017, 2019; Katju et al, 2022a; Foster et al, 2015). In vertebrates, H3K36me3 is targeted by PWWP domains in proteins contributing to homology-directed and mismatch repair, with H3K36me3 marking the gene bodies and exons of active genes (Li et al, 2013; Huang et al, 2018; Fang et al, 2021; Aymard et al, 2014; Sun et al, 2020). As predicted, reduced mutation rates in active genes, regions, and gene bodies have been observed in humans and other animals (Moore et al, 2021; Akdemir et al, 2020; Li et al, 2021; Katju et al, 2022b; Supek and Lehner, 2017).…”
Section: Introductionmentioning
confidence: 99%